Factors associated with having a steady homosexual partner among men who have sex with men, based on internet recruitment - Peng Zhang; Weiyong Chen; Jing Li; Yun Fu; Fang Wang; Xing Wang; Zhongrong Yang (Frontiers in Public Health)
ObjectiveThis study analyzed the status and factors associated with having a steady homosexual partner (HP) among men who have sex with men (MSM) to provide a scientific basis for developing prevention and control strategies for acquired immunodeficiency syndrome in this population.MethodsA questionnaire survey was conducted among study participants who were MSM recruited online by a non-governmental organization in May 2024. The participants were divided into two groups based on whether they had a steady HP. Univariate and multivariate logistic regression analyses were used to evaluate the factors influencing whether the participants had a steady HP.ResultsWe surveyed 604 participants;211 (34.93%) had a current steady HP. Multivariate logistic regression analysis showed that older participants having a steady HP (adjusted odds ratio [aOR]: 1.04; 95% confidence interval [CI]: 1.01–1.07)was associated with an average monthly income >6,000 Chinese yuan (aOR: 1.47; 95% CI: 1.01–2.16), a belief that using enhancers such as Rush Popper increases the human immunodeficiency virus (HIV) infection risk (aOR: 1.56; 95% CI: 1.02–2.41), identification as purely homosexual (aOR: 2.02; 95% CI: 1.37–2.99), having engaged in anal sex with a HP in the previous 6 months (aOR: 4.13; 95% CI:2.51–6.90), and knowing the HIV status of their HP (aOR: 1.88; 95% CI: 1.17–3.06). Participants less likely to have a steady HP had used condoms consistently during anal sex with a HP in the prior 6 months (aOR: 0.56; 95% CI: 0.35–0.90) and engaged in one-night stands with HPs (aOR: 0.44; 95% CI: 0.29–0.65).ConclusionA low proportion of participants had steady HPs (34.93%). Therefore, public education for MSM should be promoted to encourage individuals to improve their awareness of HIV infection risks. Sexual responsibility, including correct use and risks of enhancers like Rush Popper, and avoiding high-risk behaviors, such as one-night stands, is crucial to reducing the risks of HIV and sexually transmitted infections.